The Number Population of Elaeidobius kamerunicus Faust. (Coleoptera: Curculionidae) to Pollinate the Oil Palm Flowers - Linda Friscilla Jessica Hulu; Maryani Cyccu Tobing; Darma Bakti; Agus Eko Prasetyo (Universitas Sumatera Utara, 2019)
Developed-fruit was formed by pollination. One of pollination method could be composed using pollinator beetle such as Elaeidobiuskamerunicus. The objective of this research wasto study the effective of population E. kamerunicus to pollinate the palm oil flowers. It was arrange by Randomized Block Design with four treatments of bug (0, 100, 200 dan 300 adult) and six replication. The results showed that introduction of 200 adults is the most effective population in terms of fruit-bunch average weight (9.858 kg) and fruitlet average weight (7.146 kg). On the other hand, 100 adults is the most effective population amount in terms of fruit-set(56.90 %).